The Impact of Applying the Survey, Question, Re-read, Question, Construct, Question (SQRQCQ) Method on First-Grade Students’ Reading Comprehension of Narrative Texts at SMKS Teknologi YPL Lirik - Arifah, Lainul; Wahyuningsih, Destri (English Education Program, Education Faculty, Universitas Nurul Huda, 2025)
The Effect of Using Survey, Question, Re-read, Question, Construct, Question (SQRQCQ) Method Toward Students’ Reading Comprehension on Narrative Text at First Grade of SMKS Teknologi YPL Lirik. This research aims to determine the effect of using the SQRQCQ (Survey, Question, Re-read, Question, Construct, Question) method on students’ reading comprehension of narrative texts. The study employed a quantitative approach using a quasi-experimental design. The population of this research consisted of 107 first-grade students at SMKS Teknologi YPL Lirik, while the sample included 48 students divided into two groups: an experimental class (treated with SQRQCQ) and a control class (taught using conventional methods). The instrument used in this research was a reading comprehension test in the form of multiple-choice questions. The data were analyzed using an independent sample t-test with SPSS 26. The results showed that the post-test mean score of the experimental group was higher (M = 79.79) than that of the control group (M = 77.29). The t-value was 2.978 with a significance level of 0.005, indicating a significant difference between both groups. Furthermore, the Eta Squared value was 0.113, which shows a medium-to-large effect size. In conclusion, the SQRQCQ method significantly improves students’ reading comprehension on narrative texts and can be considered an effective strategy for English reading instruction at vocational high school.